Inhibition by EGTA of the formation of a biofilm by clinical strains of Staphylococcus aureus. (26th May 2013) - Liesse Iyamba, J. M.; Seil, M.; Nagant, C.; Dulanto, S.; Deplano, A.; El Khattabi, C.; Takaisi Kikuni, N. B.; Dehaye, J. P.
<x xml:space="preserve">Abstract</x> The effect of EGTA on the adhesion and on the formation of a biofilm by two reference and eight clinical strains of Staphylococcus aureus was studied. All the clinical strains were isolated from patients from Kinshasa. Spa typing confirmed that these clinical strains were distinct. The Biofilm Ring Test (BFRT®) showed that EGTA (100 µM–10 mM) inhibited the adhesion of the four clinical methicillin‐resistant (MRSA) strains and the crystal violet staining method that it inhibited the formation of a biofilm by all the strains. Divalent cations abolished the effect of EGTA on the formation of a biofilm, specially in the clinical MRSA strains. EGTA had no effect on established biofilms. Only concentrations of EGTA higher than 10 mM were toxic to eukaryotic cells. Our results establish the effectiveness and the safety of lock solutions with EGTA to prevent the formation in vitro of biofilms by S. aureus.